Dos especies nuevas de Carica - García Barriga Hernando; Hernández Camacho Jorge (Caldasia)
Carica sphaerocarpa H. García_Barriga & J. Hernández C., nov. Sp. / Carica fructifragrans H. García.Barriga & J. Hernández C., nov. sp.